Social and environmental health determinants and their relationship with parasitic diseases in asymptomatic children from a shantytown in Buenos Aires, Argentina - Garbossa, Graciela (2013)
Health inequities are a common problem for all countries and are the result of not only adverse social conditions but also poor public policies. Today chronic diseases represent the most relevant threats and are a current challenge. Parasitic infections, a leading cause of child morbidity affecting low-income populations, can be transmitted because of an unhealthy environment. Notwithstanding, scarce data have been published on the epidemiological profile of intestinal parasitoses in asymptomatic children living in shantytowns. Vulnerable populations settled in slums are growing in Argentina, particularly in Buenos Aires city. Consequently, this work intended to screen healthy carriers of enteric parasites and determine the epidemiologic profile in asymptomatic children residing in one of those communities, to explore risk factors associated with the transmission of parasites, and to initiate a basic health education campaign to promote healthy behavior in the community. Fecal samples (n = 138) were analyzed by conventional parasitological methods and a survey gathered data on symptoms, family composition, and environmental and hygiene-related variables. High prevalence of feco-orally-transmitted parasitoses (83·3%) and polyparasitism were remarkable findings. The main environmental health determinants were those related to excreta disposal and water provision. Health promotion actions were performed through the diffusion of a set of posters with iconic images and brief messages for health education. Results suggest the need for an environmental sanitation policy to complement health promotion actions. It is essential to spread the results of investigations that address inequities and social determinants of health in order to integrate data with local political processes and alert on acceptable actions for developing appropriate interventions.